Robot-assisted ultrasound imaging: Overview and development of a parallel telerobotic system. Issue 1 (March 2015) - Monfaredi, Reza; Wilson, Emmanuel; Azizi koutenaei, Bamshad; Labrecque, Brendan; Leroy, kristen; Goldie, James; Louis, Eric; Swerdlow, Daniel; Cleary, Kevin
Abstract Ultrasound imaging is frequently used in medicine. The quality of ultrasound images is often dependent on the skill of the sonographer. Several researchers have proposed robotic systems to aid in ultrasound image acquisition. In this paper we first provide a short overview of robot-assisted ultrasound imaging (US). We categorize robot-assisted US imaging systems into three approaches: autonomous US imaging, teleoperated US imaging, and human-robot cooperation. For each approach several systems are introduced and briefly discussed. We then describe a compact six degree of freedom parallel mechanism telerobotic system for ultrasound imaging developed by our research team. The long-term goal of this work is to enable remote ultrasound scanning through teleoperation. This parallel mechanism allows for both translation and rotation of an ultrasound probe mounted on the top plate along with force control. Our experimental results confirmed good mechanical system performance with a positioning error of < 1 mm. Phantom experiments by a radiologist showed promising results with good image quality.